Damage to Steel Buildings Observed after the 2011 Tohoku-Oki Earthquake. Issue 1 (March 2013) - Okazaki, Taichiro; Lignos, Dimitrios G.; Midorikawa, Mitsumasa; Ricles, James M.; Love, Jay
A joint U.S.–Japan reconnaissance team examined the damage to steel building structures caused by the 2011 Tohoku-oki earthquake. In the city of Sendai, where the peak horizontal ground acceleration exceeded 1 g, the majority of steel buildings performed well. Buildings that used older cladding systems for external finish sustained damage to their claddings even if their structural performance was excellent. Damage to a few braced frames offer insight into the seismic design of bracing connections. In areas attacked by the violent tsunami, many steel buildings stood upright after the tsunami subsided, although these buildings lost much of their external and internal finishes along with their contents. These steel buildings did not provide safe shelter for tsunami evacuation when the building submerged under the tsunami wave. A number of buildings suffered foundation failure, which was likely caused by scouring or liquefaction or a combination of multiple effects.